Host Suitability of Trichogrammatoidea Bactrae Nagaraja on Different Host Eggs - Jasti Sri Vishnu Murthy; N.S. Satpute; Mani Chellappan; Ranjith M.T (International Journal of Insects, 2024)
Trichogrammatoidea bactrae Nagaraja (Hymenoptera: Trichogrammatoidea) is a highly effective egg parasitoid for controlling lepidopteran pests. This study evaluates its host suitability and biological characteristics across various lepidopteran eggs, specifically Corcyra cephalonica Stainton (Lepidoptera: Pyralidae), Spodoptera litura Fabricius (Lepidoptera: Noctuidae), Helicoverpa armigera Hubner (Lepidoptera: Noctuidae), Spodoptera frugiperda (J.E. Smith) (Lepidoptera: Noctuidae), and Pectinophora gossypiella Saunders (Lepidoptera: Gelechiidae). The results indicate that T. bactrae shows the highest parasitization rates on C. cephalonica, followed by P. gossypiella, S. litura, H. armigera, with the lowest rate occurring on S. frugiperda. The adult emergence rate for T. bactrae is notably highest on Corcyra eggs at 92.95%, while it drops to 73.55% on S. frugiperda. The total developmental period for T. bactrae ranges from 7.22 days on C. cephalonica to 8.7 days on S. litura. Moreover, female T. bactrae consistently demonstrates a longer total life cycle compared to their male counterparts across all studied species, with the longest life cycle observed in S. litura and the shortest in C. cephalonica. Given these findings, C. cephalonica emerges as the optimal host for the factitious rearing of T. bactrae. Additionally, T. bactrae is highlighted as the most effective option for parasitizing pink bollworm eggs.
Keywords: Corcyra cephalonica; Helicoverpa armigera; Host eggs; Pectinophora gossypiella; Spodoptera frugiperda; Spodoptera litura; development and parasitization; host suitability Trichogrammatoidea bactrae